Arterial Stiffness and Long-Term Risk of Health Outcomes: The Framingham Heart Study. Issue 5 (16th February 2022) - Vasan, Ramachandran S.; Pan, Stephanie; Xanthakis, Vanessa; Beiser, Alexa; Larson, Martin G.; Seshadri, Sudha; Mitchell, Gary F.
Abstract : Background: Arterial stiffness increases with age and is associated with an increased risk of adverse outcomes on short-term follow-up (typically <10 years). Data regarding associations of arterial stiffness with health outcomes on longer-term follow-up are lacking. Methods: We evaluated 7283 Framingham Study participants (mean age 50 years, 53% women) who underwent assessment of carotid-femoral pulse wave velocity (a marker of arterial stiffness) via applanation tonometry at one or more routine examinations. We used time-dependent Cox proportional hazards regression models to relate carotid-femoral pulse wave velocity to the incidence of health outcomes (updating carotid-femoral pulse wave velocity and all covariates at serial examinations). Results: On long-term follow-up (median 15 years; minimum-maximum, 0–20), participants developed cardiometabolic disease (hypertension [1255 events]; diabetes [381 events]), chronic kidney disease (529 events), dementia (235 events), cardiovascular disease (684 events) and its components (coronary heart disease [314 events], heart failure [191 events], transient ischemic attacks or stroke [250 events]), and death (1086 events). In multivariable-adjusted models, each SD increment in carotid-femoral pulse wave velocity was associated with increased risk of hypertension (hazard ratio [HR], 1.32 [95% CI, 1.21–1.44]), diabetes (HR, 1.32 [95% CI, 1.11–1.58]), chronic kidney disease (1.19 [95% CI, 1.05–1.34]), dementia (HR 1.27 [95% CI, 1.06–1.53]), cardiovascular disease (HR, 1.20 [95% CI, 1.06–1.36]) and its components (coronary heart disease, HR 1.37 [95% CI, 1.13–1.65]; transient ischemic attack/stroke, HR, 1.24 [95% CI, 1.00–1.53]), and death (HR, 1.29 [95% CI, 1.17–1.43]). The association with heart failure was borderline nonsignificant (HR, 1.21 [95% CI, 0.98–1.51], P =0.08). Conclusions: Our prospective observations of a large community-based sample establish the long-term prognostic importance of arterial stiffness for multiple health outcomes.